Synthesis and study of transition metal oxides for supercapacitor applications - Zhao, Ting (2013)
Supercapacitor which bridges conventional capacitor and battery in the energy storage field, is gaining increasing importance due to its higher power density, good energy density, fast charge/discharge rate, plus its excellent cyclic stability. In the present work, transition metal oxide based supercapacitors, such as MnO2, Co(OH)2, and surfactant CTAB modified MnO2 (MnO2CTAB), as well as multilayer hybrid films (graphene/ MnO2, and graphene/ MnO2CTAB Our results have shown that structural directing agent in the electrochemical deposition of transition metal oxides can significantly affect the nucleation formation and growth process, the resulted microstructure, morphology and supercapacitor performance have been systematically discussed. The CTAB modified MnO), have been deposited on stainless steel substrates by electrochemical deposition method. Their crystal structures, morphologies and supercapacitor performances have been systematically studied. The effects of synthesis approaches on the structures and morphologies of transition metal oxides, as well as the correlation between structure/morphology and the corresponding supercapacitor performances are explored. In addition, the enhancement mechanisms of transition metal oxides based supercapacitors are discussed. 2 shows 3-D porous network structure with very thin nanosheet, which is much smaller than that of MnO2 prepared without the presence of CTAB, besides, the as obtained MnO2 prepared in presence of CTAB shows larger pore size and more uniform surface morphology. It is also found that the concentration of CTAB may also affects the localized electrokinetic properties near deposition surface and eventually influences the morphology and supercapacitor performance of as prepared thin film electrode. Result shows that MnO2 prepared in presence of 1wt. % CTAB has the best performance, a capacitance of 359 F g-1 at 1 A g-1 is obtained, which is larger than 297 F g-1 of MnO2. More remarkable is that MnO2 prepared in presence of 1wt. % CTAB is able to remain 100% of the initial capacitance after 1000 cycles of charge/discharge test at a current density of 10 A g-1. When the same idea of using structure directing agent to modify structure and morphology is applied to prepare Co(OH)2 for supercapacitor application, NMP modified Co(OH)2 electrode has shown similar positive result. With 20 V% addition of NMP in the pre-deposition solution, the resulted Co(OH)2 has much thinner nanosheet Supercapacitor which bridges conventional capacitor and battery in the energy storage field, is gaining increasing importance due to its higher power density, good energy density, fast charge/discharge rate, plus its excellent cyclic stability. In the present work, transition metal oxide based supercapacitors, such as MnO2, Co(OH)2, and surfactant CTAB modified MnO2 (MnO2CTAB), as well as multilayer hybrid films (graphene/ MnO2, and graphene/ MnO2CTAB Our results have shown that structural directing agent in the electrochemical deposition of transition metal oxides can significantly affect the nucleation formation and growth process, the resulted microstructure, morphology and supercapacitor performance have been systematically discussed. The CTAB modified MnO), have been deposited on stainless steel substrates by electrochemical deposition method. Their crystal structures, morphologies and supercapacitor performances have been systematically studied. The effects of synthesis approaches on the structures and morphologies of transition metal oxides, as well as the correlation between structure/morphology and the corresponding supercapacitor performances are explored. In addition, the enhancement mechanisms of transition metal oxides based supercapacitors are discussed. 2 shows 3-D porous network structure with very thin nanosheet, which is much smaller than that of MnO2 prepared without the presence of CTAB, besides, the as obtained MnO2 prepared in presence of CTAB shows larger pore size and more uniform surface morphology. It is also found that the concentration of CTAB may also affects the localized electrokinetic properties near deposition surface and eventually influences the morphology and supercapacitor performance of as prepared thin film electrode. Result shows that MnO2 prepared in presence of 1wt. % CTAB has the best performance, a capacitance of 359 F g-1 at 1 A g-1 is obtained, which is larger than 297 F g-1 of MnO2. More remarkable is that MnO2 prepared in presence of 1wt. % CTAB is able to remain 100% of the initial capacitance after 1000 cycles of charge/discharge test at a current density of 10 A g-1. When the same idea of using structure directing agent to modify structure and morphology is applied to prepare Co(OH)2 for supercapacitor application, NMP modified Co(OH)2 electrode has shown similar positive result. With 20 V% addition of NMP in the pre-deposition solution, the resulted Co(OH)2 has much thinner nanosheetSupercapacitor which bridges conventional capacitor and battery in the energy storage field, is gaining increasing importance due to its higher power density, good energy density, fast charge/discharge rate, plus its excellent cyclic stability. In the present work, transition metal oxide based supercapacitors, such as MnO2, Co(OH)2, and surfactant CTAB modified MnO2 (MnO2CTAB), as well as multilayer hybrid films (graphene/ MnO2, and graphene/ MnO2CTAB Our results have shown that structural directing agent in the electrochemical deposition of transition metal oxides can significantly affect the nucleation formation and growth process, the resulted microstructure, morphology and supercapacitor performance have been systematically discussed. The CTAB modified MnO), have been deposited on stainless steel substrates by electrochemical deposition method. Their crystal structures, morphologies and supercapacitor performances have been systematically studied. The effects of synthesis approaches on the structures and morphologies of transition metal oxides, as well as the correlation between structure/morphology and the corresponding supercapacitor performances are explored. In addition, the enhancement mechanisms of transition metal oxides based supercapacitors are discussed. 2 shows 3-D porous network structure with very thin nanosheet, which is much smaller than that of MnO2 prepared without the presence of CTAB, besides, the as obtained MnO2 prepared in presence of CTAB shows larger pore size and more uniform surface morphology. It is also found that the concentration of CTAB may also affects the localized electrokinetic properties near deposition surface and eventually influences the morphology and supercapacitor performance of as prepared thin film electrode. Result shows that MnO2 prepared in presence of 1wt. % CTAB has the best performance, a capacitance of 359 F g-1 at 1 A g-1 is obtained, which is larger than 297 F g-1 of MnO2. More remarkable is that MnO2 prepared in presence of 1wt. % CTAB is able to remain 100% of the initial capacitance after 1000 cycles of charge/discharge test at a current density of 10 A g-1. When the same idea of using structure directing agent to modify structure and morphology is applied to prepare Co(OH)2 for supercapacitor application, NMP modified Co(OH)2 electrode has shown similar positive result. With 20 V% addition of NMP in the pre-deposition solution, the resulted Co(OH)2 has much thinner nanosheet thickness and more uniform morphology, which leads to 37% increment in the capacitance of Co (OH)2 Other than modification of the MnO. 2 structure and morphology to enhance its supercapacitor performance, reducing the internal charge transfer resistance of MnO2 to promote higher capacitance has also been studied. A simple layer-by-layer potentiostatic/electrophoretic deposition technique has been developed to prepare a multilayer hybrid film consisting of alternating MnO2 and graphene layers. The as prepared multilayer hybrid film shows a capacitance as high as 396 F g-1 at 1 A g-1, and better rate capability than individual MnO2 and graphene electrode. Further characterization indicates that graphene/MnO2 multilayer hybrid structure effectively reduces internal charge transfer resistance and also has a synergetic effect on the supercapacitor performance of MnO2 Last but not least, the supercapacitor performance enhancement mechanism by modifying the morphology and reducing internal charge transfer resistance are combined to developed a graphene/CTAB modified MnO. The technique developed in this study to prepare graphene based multilayer hybrid structure is also readily generalized to many other graphene/transition metal oxide hybrid films. 2 multilayer hybrid film. The as prepared thin film exhibits a high capacitance of 403 F g-1 at 2 A g-1. Further characterization by electrochemical impedance spectroscopy shows that it has smaller internal resistance than that of MnO2. Moreover, graphene/CTAB modified MnO2 multilayer hybrid film remains 97% of the initial capacitances after 1250 cycles of charge/discharge test at a current density of 10 A g-1. Meanwhile, it is also noticed that the two capacitance enhancement mechanism may interfered with each other and a better performance can be expected with further modification.